Special Treatment of the Floating Charge in Insolvency Proceedings - Kasak, Anto (Juridica International, 2015)
In cases of insolvency, the security-holder is preferred to other creditors with respect to the outcome of sale of the object of the security. The article considers whether the preferential treatment of secured claims is justified. The situation is more complex in the case of the floating charge, because the object of the floating charge differs from that of other charges. The author maintains that the floating charge is an easy, convenient, and flexible way to secure a claim while both protecting the creditor’s interests and allowing the debtor to sell his property where necessary. On the other side, the floating charge covers almost all movable property of the debtor, which is sold in full to cover the claim. In such cases, unsecured creditors end up with nothing. Such a situation may amount to unequal treatment of unsecured creditors. For this reason, the author concludes that, relative to regular secured creditors, less preferential treatment of floating-charge holders may be justified. The author suggests creating a system for distributing a fair amount of money to the unsecured creditors on the account of the floating-charge holder’s fund.